Plantão psicológico como estratégia em saúde mental na atenção básica - LOBO, Aline Amorim (2023)
The Psychological Duty understood as a contemporary clinical modality, of welcoming and listening, presents itself as a care strategy in the field of mental health in primary health care (ABS), with a proposal of welcoming and intervention in emergency situations. This research raises a reflection on actions in mental health, between the impasses and possibilities of access to care in psychology in the scope of primary care. Recognizing the range of practice actions in different contexts, the objective of the research is to analyze the Psychological Duty as a mental health intervention strategy in PHC. Guided from the perspective of Heidegger's existential phenomenology, the understanding of the phenomena is through the clarification of the possibilities of being-in-the-world, in the deconstruction of the objectification of the theoretical-explanatory model. Therefore, this is a qualitative systematic review research, exploratory, descriptive and documentary, carried out from the survey of CAPES, SciELO and PEPSIC journals, with the descriptor "psychological duty". We understand that this research promotes a fruitful discussion about the democratization of access to mental health in PHC, the practice of social clinical psychology in public health, underlining the Psychological Duty modality as a strategy that meets the doctrinal principles of the SUS.